Сучасні методи створення і використання стереобачення - Харченко, Д. М. (ХНУРЕ, 2020)
At the moment, many scientists of the world are working on the creation of a "universal" visual system. In the course of research, we look at systems that perform any specific task in a controlled environment, issues related to processing speed and system cost. Given the sheer volume of data and the natureof the calculations required, it is often difficult to reach a satisfactory compromise between these factors
Keywords: фотограмметрія; 3D